Barriers for Using Electronic Health Records (EHRs) by Nurses in Qatar: A Cross Sectional Study - Kim Pugal; Ralph Villar; Abdulqadir J. Nashwan (Babali Nursing Research, 2021)
Introduction: Electronic Health Records (EHR) have been implemented by multiple hospitals all around the world. EHR initiatives tend to be driven by the promise of availability of patient data and enhanced system integration by the need to improve efficiency and cost-effectiveness and by a changing doctor-patient relationship towards where care is divided among a multidisciplinary members of health care professionals and/or by the need to deal with a more complex and rapidly changing environment. The aim of this research is to determine the barriers faced by nurses in Qatar in using EHRs in terms of knowledge, skills, and attitude (KSA). Methods: A survey was sent to approximately 12,000 nurses from different hospitals under Hamad Medical Corporation in Qatar through the corporation's official e-mail from January 1, 2021 to May 31, 2021. The questionnaire was developed and validated by the researcher of the study (α=0.877). The Statistical Package for the Social Sciences (SPSS) version 25.0 was used to analyze the data. Results: A total of 262 nurses participated in the study. Majority of the nurses who participated are females (69%) and ages 31-35 years old (50.4%). Among the respondents 98.5% are staff nurses with various educational levels: bachelor’s degree in Nursing (43.5 %), diploma in Nursing (27%), and Master of Arts in nursing (3.8%). Only 23.3% of the respondents have a length of service of less than 4 years; 76.7% have been with their institution more than 4 years. The majority of respondents came from the inpatient areas (37%), followed by the outpatient nurses (15.3%), and operating room nurses (14.1%). Around 91% of the respondents claimed to have a 0-3 number of trainings in the past 3 years. A significant correlation was found between age (r=-0.124, p=0.045), length of service (r=0.193, p=0.002), and area assignment (r=0.129, p=0.037) with the skill on EHR. Conclusion: Results of the study showed that the dimension of knowledge, skills, and attitude towards the use of EHR is a barrier, but only to a moderate extent. The nurses in Qatar are highly educated, well experienced and are mostly millennials. This opens a great opportunity of acceptance and amplification of EHR in Qatar with the proper training and support to nurses.